Strengthening policy engagement when scaling up interventions targeting non-communicable diseases: insights from a qualitative study across 20 countries - Ramani-Chander, Anusha; Thrift, Amanda G; van Olmen, Josefien; Wouters, Edwin; Delobelle, Peter; Vedanthan, Rajesh; Miranda, J. Jaime; De Neve, Jan-Walter; Esandi, Maria Eugenia; Koot, Jaap; Ojji, Dike; Ortiz, Zulma; et al. (Health policy and planning, 2024)
Policy engagement is an essential component of implementation research for scaling up interventions targeting non-communicable diseases (NCDs). It refers to the many ways that research team members, implementers and policymakers, who represent government decision-making, connect and interact to explore common interests. Well-conducted engagement activities foster co-production, local contextualization and assist in the successful translation of research evidence into policy and practice. We aimed to identify the challenges and facilitators to policy engagement during the early implementation phase of scale-up research studies. This qualitative study was focused on the research projects that were funded through the Global Alliance for Chronic Diseases in the 2019 round. Nineteen project teams opted to participate, with these studies implemented in 20 countries. Forty-three semi-structured stakeholder interviews, representing research, implementation and government were undertaken between August 2020 and July 2021. Transcripts were open-coded using thematic analysis to extract 63 codes which generated 15 themes reflecting both challenges and facilitators to undertaking policy engagement. Knowledge of the local government structures and trusting relationships provided the foundation for successful engagement and were strengthened by the research. Four cross-cutting concepts for engagement were identified and included: (1) the importance of understanding the policy landscape; (2) facilitating a network of suitable policy champions, (3) providing an environment for policy leaders to genuinely contribute to co-creation and (4) promoting two-way learning during researcher-policymaker engagement. We recommend undertaking formative policy analysis to gain a strategic understanding of the policy landscape and develop targeted engagement plans. Through engagement, researchers must facilitate cohesive vision and build a team of policy champions to advocate NCD research within their networks and spheres of influence. Ensuring equitable partnerships is essential for enabling local ownership and leadership. Further, engagement efforts must create a synergistic policymaker-researcher lens to promote the uptake of evidence into policy.
Online veröffentlicht: 18. November 2024
Gesehen am 23.02.2026